2012
DOI: 10.1002/hep.24708
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Lipin-1 by Ethanol: Role of AMP-Activated Protein Kinase/Sterol Regulatory Element-Binding Protein 1 Signaling in Mice

Abstract: Lipin-1 is a protein that exhibits dual functions as a phosphatidic acid phosphohydrolase (PAP) enzyme in the triglyceride synthesis pathways and a transcriptional co-regulator. Our previous studies have shown that ethanol causes fatty liver by activation of sterol regulatory element-binding protein 1 (SREBP-1) and inhibition of hepatic AMP-activated kinase (AMPK) in mice. Here, we tested the hypothesis that AMPK-SREBP-1 signaling may be involved in ethanol-mediated up-regulation of lipin-1 gene expression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 27 publications
8
139
1
Order By: Relevance
“…24 Recombinant LCN2 induced a significant, concentration-dependent increase in the TGs contents of AML-12 hepatocytes ( Figure 1A and Supplemental Figure S1A …”
Section: Lcn2 Regulates Ethanol-induced Cellular Lipid Accumulation Imentioning
confidence: 99%
See 2 more Smart Citations
“…24 Recombinant LCN2 induced a significant, concentration-dependent increase in the TGs contents of AML-12 hepatocytes ( Figure 1A and Supplemental Figure S1A …”
Section: Lcn2 Regulates Ethanol-induced Cellular Lipid Accumulation Imentioning
confidence: 99%
“…24 For pGL3-24p3/LCN2-Luciferase reporter assays, plasmids were transiently transfected into AML-12 hepatocytes by Lipofectamine reagent for 48 hours. Luciferase assays were performed with cell extracts, and the results were averaged to represent a single data point for each transfection.…”
Section: Measurement Of Intracellular Tgmentioning
confidence: 99%
See 1 more Smart Citation
“…The SREBP1c-induced increase in ACC activity directly increases fatty acid synthesis, while suppressing fatty acid oxidation. SREBP1c also upregulates lipin-1 expression and localization to the cytosol (Hu et al 2012). Within the cytosol, lipin-1 acts as a phosphatidate phosphatase, enzymatically converting phosphatidate to diacylglycerol and promoting triglyceride synthesis.…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…This inhibition plays a key role in the development of steatosis by the activation of hepatic lipogenesis, cholesterol synthesis, and glucose production in parallel with the decrease in fatty acid oxidation [74] . In rat hepatoma cells, overexpression of a constitutively active form of AMPK blocked the effect of ethanol, but in contrast, a dominant negative form augmented the effect through regulating SREBP-1 [77] . Recent data have demonstrated that Lipin-1, a Mg 2+ phosphatidate phosphatase involved in the biosynthesis of triacylglycerol and the transcriptional regulation of lipid homeostasis, is upregulated by ethanol through inhibition of AMPK and activation of SREBP-1 [78] .…”
mentioning
confidence: 93%